Pengaruh Disiplin Kerja Terhadap Kinerja Pegawai Negeri Sipil Pada Kantor Distrik Heram Kota Jayapura - Ester Saranga; Moses Yomungga (ITB AAS INDONESIA Surakarta, 2023)
The study conducted at the Heram District Office in Jayapura City, Papua, examines the correlation between work discipline and the performance of civil servants (PNS). Work discipline encompasses various elements such as punctuality, adherence to protocols, accountability for assigned tasks, and dedication to organizational objectives. A strong work discipline typically leads to enhanced employee performance as disciplined individuals tend to be more efficient, productive, and dedicated to their responsibilities. They are also more likely to accomplish tasks effectively and within set deadlines. Conversely, a lack of work discipline can impede employee performance due to negligence, errors, and a lack of focus on duties. The purpose of this study was to determine the relationship between work discipline and the performance of civil servants in Heram District. This study uses quantitative analysis methods using simple regression analysis. The results showed a t test on work discipline (X) of 2.098 with a significance level of 0.016. The statistical value of the calculated test is greater than ttable (2.098>2.042) with significantly smaller than α = 0.05 (0.016